Efektivitas Pembelajaran Daring Berbasis WhatsApp Group Berbantuan LKPD Ditinjau dari Motivasi Belajar Siswa - Wahyu Dewi Kurniawati; Tri Astuti Arigiyati; Irham Taufiq (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
This research is a quasi-experimental researchwhich aims to determine whether online learning based on WhatsApp Group with LKPD assistance is more effective than online learning based on WhatsApp Group without assistance from LKPD in terms of student learning motivation towards mathematics learning outcomes of grade VII students at SMP N 4 Sewon . The sampling technique used was cluster random sampling selected classes VII A and B. The data collection technique used a test technique in the form of a posttest, documentation for thescore pretest and a non-test technique in the form of a learning motivation questionnaire. Data were analyzed using t-test, test preconditions such normality test, mann-whitney, andtest. Kruskal WallisThe result of this research is that learning using online learning based on WhatsApp Group with the assistance of LKPD is as effective as online learning based on WhatsApp Group without assistance from LKPD and the mathematics learning outcomes of students with high motivation are better than students who have moderate and low motivation.